In-gratitude and Other Poems. - Symington, Neville (Karnac Books, 2009)
'Where does the creative act come from? No one knows. All the rash of literature in recent times from artists, scientists and theologians on the subject of consciousness finds its origin in this puzzle. Creating what has happened to one into an art form has one effect: it dissolves the barrier between the present and the past. The past is constantly stimulated into life by present experiencesparticularly when listening to someone else relating their experiences. It brings me then into a close sharing of experience with the other. Analytic theories are substitutes for these personal experiences.